Effect of low glycemic index diet on HbA1c in type 2 diabetes mellitus: A systematic review and meta-analysis in Asia - Fani Cahya Wahyuni; Ainun Nisa; Bayu Satria Wiratama; Emy Huriyati; Vina Yanti Susanti (AcTion: Aceh Nutrition Journal, 2026)
Diabetes mellitus affects 10.5% of the global population, and its prevalence is expected to increase by 2045. Type 2 diabetes mellitus (T2DM) is commonly associated with abnormal HbA1c levels, lipid metabolism, and body mass index (BMI). A low glycemic index (GI) has been proposed to improve HbA1c, lipid profiles, and BMI, but the findings remain inconsistent, and most studies have been conducted in non-Asian populations. This study evaluated the effect of a low-GI diet on HbA1c levels in Asian adults with T2DM. Systematic searches in the PubMed, ScienceDirect, and Scopus databases identified randomized controlled trials (2014-2024) involving adults (≥18 years) with T2DM, excluding pregnant and breastfeeding women. Meta-analysis and subgroup analysis were conducted, and meta-regression was used to assess the moderators.  Study quality was assessed using the ROB-2 and GRADE. Of the 1,485 articles screened, 16 met the inclusion criteria. The low-GI diet significantly reduced HbA1c and LDL levels and increased HDL levels. Subgroup analysis showed variations between the intervention and control groups, with the percentage of female participants and supplementation type as potential moderators. Despite statistical significance, the small effect size, heterogeneity, and low-to-moderate certainty of evidence (GRADE) suggest limited clinical relevance. Further research should consider the sample size, female proportion, and type of intervention in the control group to strengthen the evidence for clinical and policy applications.